When Interculturality faces a Diaspora. The Transnational Tamil Identity - Giuseppe Burgio (University of Bologna, 2016)
The Sri Lankan Tamils of the diaspora are a model of a transnational identity.From the theoretical point of view, Tamil identity challenges our mental habits and intercultural theory. If the Tamil diaspora tend to be distinguished both from the motherland and from Western, multicultural societies, then interculturality ceases to indicate a relationship between two poles, but becomes a three-pole connection, which includes the country of origin, the country of destination, and the diasporic community. The consciousness of these diasporic dynamics forces us to re-think our theoretical framework about interculturality, going beyond our actual approach based on nationally-defined concepts of society and culture. Overall, diasporas can be an excellent observation field of all transnational dynamics and through diasporas we can learn not concentrating on the migrants / residents dichotomy but focusing on people, their movements crossing national boundaries, and their specific needs.